Performance Optimization - Supana, Isra; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
Organizations should be able to improve the quality of the organization, both improving information culture and management information systems and the performance of each of its human resources. Building and developing a business in the service and consultancy sector that focuses on technology and information really requires the role of human resources. Human resources are necessary activities and have an ideal role in an organization. This research is to see the effect of implementing organizational cultural values and management information systems on employee performance with organizational commitment as an intervening variable in Bpjs Employment branch offices throughout Medan Raya. The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with a sample value of 0.411 and ap value of 0.000. Organizational Culture has a positive and significant effect on Organizational Commitment with an original sample value of 0.434 and ap value of 0.000. Organizational Commitment has a positive and significant effect on Employee Performance with the original sample being 0.339 and p values 0.000. Management Information Systems have a positive and significant effect on Employee Performance with an original sample value of 0.228 and ap value of 0.008. Management Information Systems have a positive and significant effect on Organizational Commitment with an original sample of 0.541 and ap value of 0.000. Organizational Culture has a positive and significant effect on Employee Performance through Organizational Commitment with a value of 0.147 and a value of 0.001. Management Information Systems have a positive and significant effect on Employee Performance through Organizational Commitment with an original sample value of 0.183 and ap value of 0.000.